Add Three Numbers
1+4+4=2+7+3=3+9+3=6+1+1=
6+8+9=1+8+2=0+7+7=1+1+5=
7+2+7=2+3+3=4+7+3=8+8+9=
8+5+7=2+2+3=5+4+2=5+4+4=
0+0+7=4+5+1=6+7+4=3+4+8=
7+7+5=5+4+7=9+8+6=7+3+1=
1+9+6=7+9+2=4+9+7=2+6+2=
0+3+8=8+4+7=6+9+7=7+1+3=
9+0+3=9+1+1=2+3+6=5+1+8=
1+5+7=1+3+2=2+1+1=7+1+5=
2+6+1=3+8+2=1+2+7=3+1+6=
7+7+1=5+9+6=7+1+9=6+8+2=
2+1+2=9+4+5=1+7+6=4+5+8=
8+9+7=3+7+2=9+5+6=3+1+8=
1+8+8=2+3+4=6+4+2=6+1+7=
2+5+7=6+8+8=5+7+4=1+2+5=
2+4+4=3+8+4=4+2+3=3+6+6=
5+1+1=8+4+9=5+5+5=7+7+2=
1+7+9=6+4+9=8+6+6=6+5+6=
2+9+3=3+2+1=6+2+8=8+2+3=
4+5+7=8+2+1=6+8+6=5+7+3=